Translating the complexity of disaster resilience with local leaders - Wowk, Kateryna; Adams, Margaret; Martinez, Emily (Frontiers in Communication, 2023)
Disaster resilience involves a complex web of processes, policies, regulatory requirements, and data that is difficult—if not impossible—to fully comprehend, even by seasoned experts. Yet resilience is not owned by “experts”—it is owned by local communities. Local leaders must be empowered to understand and trained to skillfully navigate complex systems to strengthen and continually build their resilience. Similarly, though billions of dollars in federal disaster recovery and mitigation funds are available to help local communities strengthen their resilience, additional work is needed to communicate, understand, assess, and address vulnerabilities at the local level, and particularly in small towns and in underserved communities, by harnessing local knowledge and data. In this article we present a framework developed to guide locally-owned resilience in Texas following Hurricane Harvey. The case study discusses methodologies to enhance the granularity of existing tools that assess resilience and social vulnerability by focusing on the local context for each, while building institutional to individual leadership needed to build disaster resilience over the longer-term. In particular, we discuss approaches being advanced by the Regional Resilience Partnership, which was formed to strengthen capacity for resilience in the 11 county Coastal Bend region, where Harvey first made landfall.